EFFECTS OF HIGH-PERFORMANCE WORK SYSTEMS (HPWS) ON ORGANIZATIONAL AMBIDEXTERITY: MEDIATING EFFECT OF EMPLOYEE FUNCTIONAL FLEXIBILITY - Jameel Afsar; Dr Anum Tariq (International Journal of Contemporary Issues in Social Sciences, 2024)
The motive of this study is to identify the relationship among high-performance work systems (HPWS) of manufacturing sector in Pakistan with organizational ambidexterity within the companies, the mediating effect of functional flexibility has also been measured. This research is based on AMO theory, which has been extended by adding workforce agility and technology adoption. Quantitative research methods have been applied in order to fulfill the purpose of this study, data has been collected from the top and middle level management of the textile industry of the Pakistan. Stratified sampling technique has been used and adopted questionnaires has been distributed among 500 employees of the companies, 450 responses were returned in which 416 responses were found valid. The findings shown that HPWS has positive relationship with organizational ambidexterity but motivation and opportunity have no relationship with OA. Moreover, functional flexibility partially mediates the relationship of workforce agility, technology adoption, ability with organizational ambidexterity, while no mediation has been proved among the relationship of motivation and opportunity with organizational ambidexterity.